Competition between formation of Al2O3 and Cr2O3 in oxidation of Al0.3CoCrCuFeNi high entropy alloy: A first-principles study. (15th July 2019) - Hong, Yu; Beyramali Kivy, Mohsen; Asle Zaeem, Mohsen
Abstract: We studied the oxidation behavior of face-centered cubic Al0.3 CoCrCuFeNi high entropy alloy through first-principles calculations. Three surface orientations were chosen for oxidation, and all the possible combinations of atomic positions at these surfaces were considered. The adsorption energy of oxygen adhesion to the studied surfaces was the lowest for the sites with more neighboring Cr atoms, and the second most favorite site for oxygen adsorption had more neighboring Al atoms. On the other hand, the calculated cohesive energies of oxides indicated that Al formed the most stable oxide among other alloying elements, and Cr formed the second most stable oxide. Graphical abstract: Unlabelled Image